Women’s Healthy Body Image and the Mother-Daughter Dyad - McBride, Hillary L.; Kwee, Janelle L.; Buchanan, Marla J. (Canadian Journal of Counselling and Psychotherapy, 2017)
Owing to the prevalence of body dissatisfaction and disordered eating among North American women, this study was designed to better understand young women’s development of healthy body image and embodiment, including the role that mothers play. Using the Listening Guide, a qualitative method of analysis, themes were identified in the interviews of 10 participants, representing 5 mother-daughter dyads in which the daughters were young adult women with healthy body images. Results suggest that mothers supported their daughters in nonappearance domains, while also celebrating their daughters’ beauty, through relational safety and connection. Spirituality is also discussed as it relates to the development of healthy embodiment.